(untitled) (Fractal: Journal of Psychology, 2009)
This essay takes the event urban as symptom of the city. What is the suffering of the city? Excess of individualism and the weakness of public life. But if what characterizes the city is the shelter of the Other with sociability, can we think a city without the question of the hospitality? The contradiction between city and individualism, and privacy and hospitality, I observe in our streets, from certain urban scenes, inferring from there what these scenes can tell us of the ethos of the city. They show to many things of a new urban landscape/human. A landscape that insists on disarranging the image of the shelter as the central scene of the city, imposing its obscene truth, its obscene scene.